Penerapan Good Corporate Governnace dalam Optimalisasi Tata Kelola Pelayanan Perum Damri Cabang Surabaya - Muhammad Chasan Amrulloh; Tukiman Tukiman (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
The purpose of this study is to describe the application of good corporate governance in optimizing service governance in the perum damri branch of the City of Surabaya. This research method uses a descriptive type of qualitative research with data collection techniques carried out through observation techniques, interviews, documentation, and previous research. The results showed that the Perum damri Branch of Surabaya City has not fully applied the principles of good corporate governance as a whole from the 5 principles of achieving goals, there is still 1 principle that is well implemented, namely the principle of independency. Transparency has not been carried out due to the absence of operational information services, accountability has not been fully implemented, there is still no guarantee of employee competence and the company governance system has not run optimally, responsibility has not been fully relaxed due to the absence of social impact programs for the community in the company environment, fairness has not been fully implemented because the community complaint box facility is still not available and there are still many fleets for rejuvenation and fleets are carried out for people with disabilities.